Toward a New Vision of Equality: Perspectives of Male Teachers in the Elementary Music Classroom. (October 2017) - Lesser, Andrew
Research concerning men working in predominantly female environments has suggested that stereotyping can occur when gender norms are violated, such as men teaching at the elementary school level. The present study investigated the presence and perspectives of male elementary school music teachers in specific geographical regions of the Northeastern United States. A qualitative analysis of six public school districts representing multiple states in the Northeastern United States revealed that women still hold a majority among elementary music teachers. Interviews were then conducted with three selected male elementary music teachers to determine if any of them felt discriminated or marginalized among their female colleagues. While these men did claim that their masculinity indeed caused various issues relating to male discrimination, all three felt content with their positions regardless of their gender identification.